Library usage patterns of the University of Perpetual Help System DALTA as affected by factors on students' personal attributes, background characteristics, faculty, user needs, library resources, services and facilities - Orillaza, Jose Miguel G.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
This study deals with library usage patterns of the University of Perpetual Help System DALTA as affected by factors on students' personal attributes, background characteristics, faculty, user needs, library resources, services and facilities of the UPHSD Library and Media Center. Specifically, the study aimed to determine: (1) how students' personal attributes such as age, gender, year level, academic performance, academic load, income level and distance of residence from campus affect library usage, (2) how background characteristics in terms of students' previous library experience, familiarity in using libraries, library instruction attended, library orientation attended and computer literacy affect library usage, (3) how faculty members affect library usage through their encouragement, course/subject requirements and student-faculty interactions, (4) how users' perceived needs affect library usage and (5) how students assessment of the UPHSD Library and Media Centers' resources, services and facilities affect library usage.
The study is limited to the undergraduate students who were enrolled during the first academic job 2010-2011 and have used the UPHSD Library and Media Center. The study is descriptive as well as qualitative. However, quantitative analysis was also done to validate qualitative results. Data resulting from the survey was analyzed using the Likert scale, frequencies and distributions.
It was first found out that age, year level, academic performance, academic load and distance of residence from campus had a significant correlation with the library usage patterns, while gender and income level only had a partial significant correlation with the library usage patterns. Second; familiarity with using libraries had a significant correlation with the library usage patterns, while previous library experience, library orientation attended, library instruction attended and computer literacy had a partial significant correlation with the library usage patterns. Third; encouragement of faculty members had a significant correlation with the library usage patterns, while course/subject requirements and student-faculty interaction had only a partial significant correlation with the library usage patterns. Fourth; for all the respondents from the colleges of the UPHSD, except for the College of International and Hospitality Management and the College of Arts and Science, a significant correlation between their perceived needs and their library usage patterns. Fifth; it was found out that accessibility of library resources had a significant correlation with the library usage patterns. The availability, adequacy, students' satisfaction and awareness of the library resources had a partial significant correlation with the library usage patterns. Sixth, the helpfulness of staff and services, students' satisfaction an awareness of the library services also had a partial significant correlation with the library usage patterns. However, there was no significant correlation between the adequacy of library facilities and the library usage patterns.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of Perpetual Help System DALTA -- Students -- Use studies